2013
DOI: 10.1007/s00270-013-0570-x
|View full text |Cite
|
Sign up to set email alerts
|

MR-guided Periarterial Ethanol Injection for Renal Sympathetic Denervation: A Feasibility Study in Pigs

Abstract: MR-guided periarterial ethanol injection was feasible and efficient for renal sympathetic denervation in a swine model. This technique may be a promising alternative to the catheter-based approach in the treatment of resistant arterial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…Initial animal experiments and clinical studies (simplicity HTN-1 and 2 clinical trials) confirmed the effectiveness of this method [9,33,34]. However, endovascular RFA has several procedural limitations, including that not all hypertensives are suitable for this method and that patients must have a specific vascular anatomy [15,17]. Outcomes in controlling BP were also variable in several studies [9][10][11]36] with a recent clinical trial showing no significant difference in BP reduction between RFA and sham-treated patients after 6 months [37].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Initial animal experiments and clinical studies (simplicity HTN-1 and 2 clinical trials) confirmed the effectiveness of this method [9,33,34]. However, endovascular RFA has several procedural limitations, including that not all hypertensives are suitable for this method and that patients must have a specific vascular anatomy [15,17]. Outcomes in controlling BP were also variable in several studies [9][10][11]36] with a recent clinical trial showing no significant difference in BP reduction between RFA and sham-treated patients after 6 months [37].…”
Section: Discussionmentioning
confidence: 94%
“…NE concentration in renal parenchyma was used to assess the effectiveness of the method, as follows: Immediately after removal, kidneys were frozen at -70°C. After thawing using a sonicator, NE measurement was performed using high performance liquid chromatography as previously described [17,26]. Serum Cr level was measured in all animals after the intervention.…”
Section: Intervention Procedures For Rsdmentioning
confidence: 99%
See 1 more Smart Citation
“…In a clinical study of catheter-based radiofrequency ablation the mean reduction in renal NE spillover was 47% [4] . MR-guided periarterial ethanol injection also found a significant reduction of NE concentration in the kidney parenchyma of 53% [30] . Circumferential adventitial delivery of 0.15, 0.30 and 0.60 ml of ethanol injection caused a mean renal NE reduction of 54, 78 and 88%, respectively [31] .…”
Section: Color Version Available Onlinementioning
confidence: 96%
“…The sympathetic nervous system is tightly bundled within the perirenal space and is accessible under percutaneous needle guidance using MR imaging, CT, or US (69,70). Preliminary studies of RDN using image-guided, percutaneous instillation of sclerosants suggest similar results to endovascular ablation techniques (70).…”
Section: Other Minimally Invasive Htn Therapiesmentioning
confidence: 99%